Sestrin2 Attenuates Myocardial Endoplasmic Reticulum Stress and Cardiac Dysfunction During Ischemia/Reperfusion Injury - Xuan Li; Zhen Wang; Alan J. Mouton; Ana C. M. Omoto; Alexandre A. da Silva; Jussara M. do Carmo; Ji Li; John E. Hall (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Sesn2 (Sestrin2) is a stress‐induced protein that provides protective effects during myocardial ischemia and reperfusion (I/R) injury, while endoplasmic reticulum (ER) stress may be a pivotal mediator of I/R injury. The goal of this study was to determine whether Sesn2‐mTOR (mammalian target of rapamycin) signaling regulates ER stress during myocardial I/R. Methods and Results In vivo cardiac I/R was induced by ligation and subsequent release of the left anterior descending coronary artery in wild‐type (WT) and cardiac‐specific Sesn2 knockout (Sesn2cKO) mice. At 6 hours and 24 hours after reperfusion, cardiac function was evaluated, and heart samples were collected for analysis. I/R induced cardiac ER stress and upregulated Sesn2 mRNA and protein levels. Inhibiting ER stress with 4‐phenylbutyric acid reduced infarct size by 37.5%, improved cardiac systolic function, and mitigated myocardial cell apoptosis post‐I/R. Hearts from Sesn2cKO mice displayed increased susceptibility to ER stress during I/R compared with WT. Notably, cardiac mTOR signaling was further increased in Sesn2cKO hearts compared with WT hearts during I/R. In mice with cardiac Sesn2 deficiency, compared with WT, ER lumen was significantly expanded after tunicamycin‐induced ER stress, as assessed by transmission electron microscopy. Additionally, pharmacological inhibition of mTOR signaling with rapamycin improved cardiac function after tunicamycin treatment and significantly attenuated the unfolded protein response and apoptosis in WT and Sesn2cKO mice. Conclusions Sesn2 attenuates cardiac ER stress post‐I/R injury via regulation of mTOR signaling. Thus, modulation of the mTOR pathway by Sesn2 could be a critical factor for maintaining cardiac ER homeostasis control during myocardial I/R injury.